2020
DOI: 10.1242/jcs.235838
|View full text |Cite
|
Sign up to set email alerts
|

Topical insulin application accelerates diabetic wound healing by promoting anti-inflammatory macrophage polarization

Abstract: Besides regulating glucose levels, insulin has been reported to participate actively in many other functions such as modulating inflammatory reaction. In this study we investigated how insulin application topically would effort the diabetic wound healing process. We found that the excessive expression of insulin degrading enzyme in diabetic skin led to the insufficient insulin level in diabetic skin during the wound healing, which ultimately reduced the recovery rate of diabetic wounds. We confirmed the topica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…These inflammatory mediators are important for inducing the adaptive immune response and therefore may explain the increased susceptibility to invading pathogens in people with diabetes [109] . This evidence suggests that insulin treatment may reestablish immune function by improving phagocytosis and chemotaxis, bactericidal capacities of neutrophils [120] , [121] and consequently supporting the significance of sufficient blood glucose management during COVID-19.…”
Section: Alterations Of the Immune System In People With Diabetes And Sars-cov-2 Infectionmentioning
confidence: 68%
“…These inflammatory mediators are important for inducing the adaptive immune response and therefore may explain the increased susceptibility to invading pathogens in people with diabetes [109] . This evidence suggests that insulin treatment may reestablish immune function by improving phagocytosis and chemotaxis, bactericidal capacities of neutrophils [120] , [121] and consequently supporting the significance of sufficient blood glucose management during COVID-19.…”
Section: Alterations Of the Immune System In People With Diabetes And Sars-cov-2 Infectionmentioning
confidence: 68%
“…PM promotes macrophage infiltration in the process of diabetic wound healing, which is at least partly related to the reduced formation of MGO‐derived AGEs. Phagocytosis of macrophages is considered to be crucial for the resolution of inflammation and the initiation of wound repair 19,38 . In vitro, we discovered that the phagocytic function of M1 macrophages was damaged by MGO, which could be reversed by the administration of PM.…”
Section: Discussionmentioning
confidence: 99%
“…Phagocytosis of macrophages is considered to be crucial for the resolution of inflammation and the initiation of wound repair. 19,38 In vitro, we discovered that the phagocytic function of M1 macrophages was damaged by MGO, which could be reversed by the administration of PM. Interestingly, the phagocytosis of macrophages with an M0 or M2 phenotype was not affected by MGO.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Duckworth and colleagues reported that diabetic patients with worse outcomes (i.e., amputation of extremities) had higher wound fluid insulin degradation than fluid from non-diabetic patients [ 183 ]. Conversely, Yang and colleagues showed increased expression of IDE in the skin of diabetics during wound healing, which was associated with impaired wound healing [ 206 ]. Taken together, these observations suggest that inhibition of IDE activity may be a valid therapeutic approach for promoting wound healing.…”
Section: Activation Vs Inhibition As a Therapeutic Strategymentioning
confidence: 99%